“Seri Cerita Empatiku”: Dialogic Reading Method to Develop Empathy in 5-7 Years Old Children - Nadia, Yasmin; Salim, Rose Mini Agoes (FKIP Universitas Lampung, 2025)
“Seri Cerita Empatiku”: Dialogic Reading Method to Develop Empathy in 5-7 Years Old Children. Objective: The prevalence of aggressive behaviors in early childhood children needs significant attention due to its potential negative impact on both the children themselves and those around them. Empathy, a crucial component of prosocial behavior, is an important factor that can be cultivated in early childhood to counteract aggressive tendencies. This study aims to foster empathy in children aged 5–7 years through the dialogic reading method. The intervention focuses on two primary aspects: enhancing children’s ability to recognize emotional expression (e.g., happiness, sadness, anger, and fear) and promoting empathy by developing cognitive and affective empathy. Methods: The research was conducted with 15 children using the Empathy Scale for Children to measure emotional understanding and the Empathy Continuum Scoring System to measure empathy. The Empathy Scale for Children and the Empathy Continuum Scoring System were translated into Indonesian and adapted for children aged 5-7 years. The book reading intervention using the dialogic reading method was carried out for 3 sessions. In the book reading session, children were divided into small groups of 5-7 children. There were 2 story books read in this study, namely